Guiding Opioid Administration by 3 Different Analgesia Nociception Monitoring Indices During General Anesthesia Alters Intraoperative Sufentanil Consumption and Stress Hormone Release: A Randomized Controlled Pilot Study. (May 2020) - Funcke, Sandra; Pinnschmidt, Hans O.; Wesseler, Stefan; Brinkmann, Charlotte; Beyer, Burkhard; Jazbutyte, Virginija; Behem, Christoph R.; Trepte, Constantin; Nitzschke, Rainer
Abstract : BACKGROUND: This pilot study investigated the effect of sufentanil titration by 3 different analgesia monitoring devices or clinical signs during general anesthesia. METHODS: Forty-eight patients undergoing radical retropubic prostatectomy with sevoflurane/sufentanil anesthesia were randomly assigned into 4 groups and received sufentanil guided either by 1 of 3 analgesia monitoring devices (Surgical Pleth Index [SPI], Pupillary Pain Index [PPI], Nociception Level [NoL]) or by clinical judgment (control). The primary end point was intraoperative sufentanil consumption. Adrenocorticotropic hormone (ACTH) and cortisol were measured at 4 time points during the day of surgery. Data were analyzed by Kruskal–Wallis and Mann–Whitney U tests and by mixed model and area under the curve (AUC) analyses for group comparisons and time effects of stress hormones. RESULTS: The total amount of sufentanil administration (μg·kg −1 ·minute −1 ·10 −3 ) differed between the groups (median [quartiles]: control = 5.6 [4.4–6.4], SPI = 7.2 [4.8–8.4], PPI = 2.0 [1.8–2.9], NoL = 3.8 [3.3–5.1]; PPI versus SPI, −5.1 [−6.6 to −1.3], P < .001; NoL versus SPI, −3.0 [−5.2 to 0.2], P = .024; control versus SPI, −1.6 [−3.7 to 1.7], P = .128; NoL versus PPI, 1.7 [0.6–3.4], P < .001; control versus PPI, 3.4 [2.0–4.6], P < .001; control versus NoL, 1.6 [−0.2 to 3.3], P = .017) (Hodges–Lehmann estimator [99% confidence interval CI], P values). The AUC analysis indicated differences among groups in cumulative ACTH levels (ng·liter −1 ·minute, natural logarithm (ln)-transformed data) of NoL versus PPI (−1.079 [−1.950 to −0.208], P = .001) and PPI versus SPI (1.192 [0.317–2.068], P = .001), as well as differences in cortisol levels (µg·liter −1 ·minute) for PPI versus SPI (46, 710 [21, 145–72, 274], P < .001), NoL versus SPI (27, 645 [3163–52, 126], P = .003), and control versus SPI (31, 824 [6974–56, 675], P = .001) (differences in means [99% CI], P value). Secondary end points (postoperative recovery, pain level, and analgesia medication) showed no differences. CONCLUSIONS: The type of analgesia nociception monitoring affected the total amount of sufentanil administered. Lower sufentanil doses in the PPI group were associated with an increased endocrine stress response. Titration by SPI caused no opioid reduction compared to the control but was associated with a reduced endocrine stress response.